Analisis Keputusan Konsumen Untuk Pembelian Kopi di Metime Coffe And Eatery Kota Bengkulu - Rita Feni; sunita mardianti; Elni Mutmainnah; Edi Efrita; Maheran Mulyadi; Edy Marwan (Jurnal MeA (Media Agribisnis), 2022)
The development of Coffee beverage in coffee stall create coffee drinking as a lifestyle and as a way to show prestige. This lifestyle create business opportunity for coffee shop owner to give best service to costumer. One method to see customer respond is by doing market analysis with attribute approach. This study aimed to know the customer characteristic, customer satisfactory index and coffee attribute that important for the customer of Metime Coffe and Eatery Bengkulu. The sample used 152 respondent collected using accidental sampling. Data analysis used was descriptive analysis, customer satisfaction index (CSI) and Importance and Performance analysis (IPA). The study comcluded that customer was mostly women aged from 17-46 years, with income < Rp 500.000,-. Customer satisfaction Index score is 88,85% which means that customer was very satisfy with coffee shop services. IPA score showed that coffee shop sit in quadrant 1 which means improvement in performance was needed such as, WiFi, price that suited the product size, location, safe and large parking spot, handwashing facility, and a good coffee with strong smell.